Vasculitis masquerading as a mass: a case report of Takayasu arteritis in a 28-year-old male - Sirohi, Parmendra; Sharma, Peeyush; Gupta, Rahul; Vishwakarma, Manaswi (International Journal of Research in Medical Sciences, 2024)
Takayasu arteritis is a chronic vasculitis mainly involving the aorta and its main branches most commonly subclavian and carotid. It induces clinically varied ischaemic symptoms due to stenotic lesions or thrombus formation, including blindness, retinal haemorrhage, pulselessness, aortic regurgitation and congestive heart failure due to dilatation of the ascending aorta. More acute progression causes destruction of arterial wall, leading to the formation of aneurysms and rupture of the involved arteries. Here we present a case of Takayasu’s arteritis in a 28-year-old male who presented with nonspecific symptoms of fever and neck pain with palpitations and feeling of pulsations in right side of neck since last 20 days and was eventually diagnosed as arteritis. This case shows that it can present with many non-specific symptoms and can be diagnosed with proper examination and a high index of suspicion due to its nonspecific overlapping features with many diseases.